2006
DOI: 10.1096/fj.06-6837com
|View full text |Cite
|
Sign up to set email alerts
|

BMP‐7 functions as a novel hormone to facilitate liver regeneration

Abstract: Bone morphogenic protein-7 (BMP-7) is a key protein involved in liver organogenesis and development. The physiological circulating concentration of BMP-7 is between 100 and 300 pg/ml. BMP-7 expression is absent in the liver, but the receptors for BMP-7 are present on adult hepatocytes. Therefore, we hypothesized that BMP-7 might function as an endogenous regulator of adult hepatocyte proliferation and liver homeostasis. Here, we demonstrate that neutralization of circulating endogenous BMP-7 results in signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
108
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(116 citation statements)
references
References 24 publications
6
108
1
1
Order By: Relevance
“…Although the liver does not normally produce BMP7, BMP7 receptors are found on hepatocytes, and neutralization of circulating BMP7 in a mouse partial hepatectomy model inhibited hepatocyte regeneration (54). In the reverse experiment, these authors demonstrated increased liver proliferation after partial hepatectomy when recombinant BMP7 was infused into the mice.…”
Section: Discussionmentioning
confidence: 99%
“…Although the liver does not normally produce BMP7, BMP7 receptors are found on hepatocytes, and neutralization of circulating BMP7 in a mouse partial hepatectomy model inhibited hepatocyte regeneration (54). In the reverse experiment, these authors demonstrated increased liver proliferation after partial hepatectomy when recombinant BMP7 was infused into the mice.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulated evidence suggested that BMP-7 signaling was beneficial to resolve established organ damage, especially renal and hepatic progressive fibrosis (Wang et al 2006;Sugimoto et al 2007;Zeisberg and Kalluri 2008). Of note, small peptide agonists of BMP-7 receptors have been developed to inhibit kidney inflammation, tissue damage, and fibrosis (Sugimoto et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, small peptide agonists of BMP-7 receptors have been developed to inhibit kidney inflammation, tissue damage, and fibrosis (Sugimoto et al 2007). However, to date, no small regulator targeting the myocardial fibrosis was reported.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous growth factors and cytokines have been implicated in the initiation and control of this regenerative response [1,[10][11][12][13][14][15][16], with the activation of seemingly critical transcription factors, such as AP-1, NFκB and STAT-3. Liver injury can be associated with a defective intestinal barrier, leading to exposure to bacterial products such as lipopolysaccharides and components of the innate immune system (complement fragments), and their activation of the NFκB pathway in Kupffer cells, leading to the production and secretion Figure 1.…”
Section: Hepatocytesmentioning
confidence: 99%